Unlocking the potential of neuromuscular electrical stimulation: achieving physical activity benefits for all abilities - Ackermann, Paul W.; Juthberg, Robin; Flodin, Johanna (Frontiers in Sports and Active Living, 2024)
Neuromuscular Electrical Stimulation (NMES) uses electrical impulses to induce muscle contractions, providing benefits in rehabilitation, muscle activation, and as an adjunct to exercise, particularly for individuals experiencing immobilization or physical disability. NMES technology has significantly progressed, with advancements in device development and a deeper understanding of treatment parameters, such as frequency, intensity, and pulse duration. These improvements have expanded NMES applications beyond rehabilitation to include enhanced post-exercise recovery, improved blood glucose uptake, and increased lower limb venous return, potentially reducing thrombotic risks.Despite its benefits, NMES faces challenges in user compliance, often due to improper electrode placement and discomfort during treatment. Research highlights the importance of optimizing stimulation parameters, including electrode positioning, to improve both comfort and treatment efficacy. Recent innovations, such as automated processes for locating optimal stimulation points and adaptable electrode sizes, aim to address these issues. When combined with wearable technologies, these innovations could improve NMES treatment adherence and deliver more consistent, long-term therapeutic outcomes for patients with various physical limitations. Together, these developments indicate a promising future for NMES, presenting a valuable tool to enhance the benefits of physical activity across diverse populations, from rehabilitative care to broader health and wellness applications.